On Sombor indices of line graph of silicate carbide Si2C3-I[p, q]. (2nd January 2022) - Asif, Fatima; Zahid, Zohaib; Husin, Mohamad Nazri; Cancan, Murat; Taş, Ziyattin; Alaeiyan, Mehdi; Farahani, Moahmmad Reza
Abstract: Topological indices are numerical parameters associated with underlying topology of a molecular structure. They are correlated with several physio-chemical properties of chemical compounds. Recently, Euclidean metric based topological index has been introduced named as Sombor index. Therefore, in this article, we will discuss combinatorial aspects and compute Sombor index, average Sombor index and the reduced Sombor index of line graph of silicate carbides Si 2 C 3 -I [ p, q ].